GE_GERICHTE P/15661/2017 vom 4. Februar 2019 - GE Cour de justice (2019)
DÉTENTION PROVISOIRE ; INDEMNITÉ(EN GÉNÉRAL) ; CLASSEMENT DE LA PROCÉDURE ; DÉFENSE D'OFFICE ; INDEMNITÉ(EN GÉNÉRAL) | CPP.429; CPP.431.al2; CPP.135